Mig-6 deficiency cooperates with oncogenic Kras to promote mouse lung tumorigenesis. (October 2017) - Liu, Jian; Cho, Sung-Nam; Wu, San-Pin; Jin, Nili; Moghaddam, Seyed Javad; Gilbert, Jennifer L.; Wistuba, Ignacio; DeMayo, Francesco J.
Highlights: Mig-6 deficiency promotes the development of Kras G12D -induced mouse lung adenoma. MIG-6 deficiency attenuates apoptosis of lung adenoma expressing KRAS G12D . Total and phosphorylated ERBB4 is increased in adenoma of Mig-6 d/d Kras G12D lung. Ablation of ERBB4 increases apoptosis of lung adenocarcinoma cells ( MIG-6 −/− KRAS G12D ). Abstract: Objectives: Lung cancer is the leading cause of cancer related deaths worldwide and mutation activating KRAS is one of the most frequent mutations found in lung adenocarcinoma. Identifying regulators of KRAS may aid in the development of therapies to treat this disease. The mitogen-induced gene 6, MIG-6, is a small adaptor protein modulating signaling in cells to regulate the growth and differentiation in multiple tissues. Here, we investigated the role of Mig-6 in regulating adenocarcinoma progression in the lungs of genetically engineered mice with activation of Kras . Materials and methods: Using the CCSP Cre mouse to specifically activate expression of the oncogenic Kras G12D in Club cells, we investigated the expression of Mig-6 in CCSP Cre Kras G12D -induced lung tumors. To determine the role of Mig-6 in Kras G12D -induced lung tumorigenesis, Mig-6 was conditionally ablated in the Club cells by breeding Mig6 f/f mice to CCSP Cre Kras G12D mice, yielding CCSP Cre Mig-6 d/d Kras G12D mice ( Mig-6 d/d Kras G12D ). Results: We found that Mig-6 expression is decreased in CCSP Cre Kras G12D -induced lung tumors. Ablation of Mig-6 in the Kras G12D background led to enhanced tumorigenesis and reduced life expectancy. During tumor progression, there was increased airway hyperplasia, a heightened inflammatory response, reduced apoptosis in Kras G12D mouse lungs, and an increase of total and phosphorylated ERBB4 protein levels. Mechanistically, Mig-6 deficiency attenuates the cell apoptosis of lung tumor expressing KRAS G12D partially through activating the ErbB4 pathway. Conclusions: In summary, Mig-6 deficiency promotes the development of Kras G12D -induced lung adenoma through reducing the cell apoptosis in Kras G12D mouse lungs partially by activating the ErbB4 pathway.